2015
DOI: 10.1007/s00428-015-1723-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor shrinkage versus fragmentation following radiochemotherapy and surgery for rectal cancer

Abstract: Most patients with rectal cancer receive neoadjuvant radiochemotherapy (RCT), causing a variable decrease in tumor mass. We evaluated the prognostic impact of pathologic parameters reflecting tumor response to RCT, either directly or indirectly. Seventy-six rectal cancer patients receiving neoadjuvant RCT between 2006 and 2009 were included. We studied the association between disease-free survival (DFS) and the "classical" clinicopathologic features as well as tumor deposits, circumferential resection margin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…The limited size of the fragments is below the power of resolution on imaging and surgical treatment might be irradical, resulting in local recurrences. Three recent studies (289 patients with locally advanced rectal cancer) [68][69][70] showed that fragmentation was present in 40% of cases, while in a study of 45 cT3 patients from Cleveland [44] 80% of cases showed fragmented response. Fragmentation or scattering of tumour cells also causes a clear discrepancy between macroscopy and microscopy [71].…”
Section: Patterns Of Tumour Response: Fragmentation Versus Shrinkagementioning
confidence: 94%
See 3 more Smart Citations
“…The limited size of the fragments is below the power of resolution on imaging and surgical treatment might be irradical, resulting in local recurrences. Three recent studies (289 patients with locally advanced rectal cancer) [68][69][70] showed that fragmentation was present in 40% of cases, while in a study of 45 cT3 patients from Cleveland [44] 80% of cases showed fragmented response. Fragmentation or scattering of tumour cells also causes a clear discrepancy between macroscopy and microscopy [71].…”
Section: Patterns Of Tumour Response: Fragmentation Versus Shrinkagementioning
confidence: 94%
“…In a careful description of the findings in 27 patients (49%), it was shown that fragments could be found up to 3 cm from the ulcer, in all directions (proximal, distal and lateral). Fragmentation is associated with more frequent residual lymph node metastases, less downstaging, positive resection margins and a poor outcome [68][69][70]. When TRG was applied to these cases [69], there was no prognostic impact.…”
Section: Patterns Of Tumour Response: Fragmentation Versus Shrinkagementioning
confidence: 99%
See 2 more Smart Citations
“…We feel that the explanation for this apparent discordance between MRI estimation of response and histopathological regression can be the pattern of regression. A recent report by Hav et al (17) has evaluated this issue in a sample of 76 rectal carcinoma patients receiving CRT. These authors concluded that tumor shrinkage is prognostically different from tumor fragmentation and this can explain the worse predictive power of regression compared to down-staging.…”
Section: Discussionmentioning
confidence: 99%